Augmentation mammoplasty and autologous fat transplantation: an alternative for the treatment of hypomastia and mild pectus excavatum - Case report - Marcus Vinicius Jardini Barbosa; Barbara Rodrigues Batista; Fabio Xerfan Nahas; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica, 2023)
Pectus excavatum(PE) is a congenital chest deformity characterized by deep depression in the sternum. Autologous fat transplantation has been used for aesthetic purposes, mainly on the face, and has recently gained relevance in thoracic and breast surgeries. The present study aims to present a case of mild PE associated with hypomastia. A 24-year-old female patient attended the consultation for breast augmentation due to hypomastia, but the clinical examination also revealed an associated mild PE that the patient did not notice. Surgical planning included breast augmentation and autologous fat transfer. A 260ml silicone breast implant was used, and 250ml of fat was injected in the sternal region and the lower medial contour of the breasts. There were no complications during the 12-month follow-up period. The combination of augmentation mammoplasty and fat transplantation in treating PE deformity proved to be a minimally invasive, good, safe option with high patient satisfaction.